Corporate social responsibility as a strategic lever: Enhancing perceived quality and brand equity in emerging banking industry - Pham, Hung Manh; Ngo, Nga Thi; Nguyen, Minh Nhat (Edelweiss Applied Science and Technology, 2025)
This study explores the strategic role of corporate social responsibility (CSR) in shaping customer perceptions, trust, and brand equity in Vietnam’s emerging banking sector. The research aims to assess how CSR initiatives influence perceived service quality and brand effects, particularly through the mediating role of trust. Adopting a quantitative research design, data were collected from 398 banking customers and employees in Hanoi and analyzed using partial least squares structural equation modeling (PLS-SEM). The findings reveal that CSR significantly enhances perceived service quality, builds trust, and strengthens brand equity. Trust plays a critical mediating role between service quality and brand impact, highlighting its importance in fostering customer loyalty. The study concludes that CSR is not merely a reputational tool but a strategic asset that contributes to long-term brand development and customer engagement. Practical implications include recommendations for banks to align CSR initiatives with community needs and environmental goals to enhance customer trust and loyalty. This research contributes to CSR and branding literature by offering empirical evidence from an emerging market context, with actionable insights for sustainable banking practices.